Proposed model of strategic management applying the scorecard for improving the performance of the company Kaniman Srl. from the of Pucallpa city 2012 - Bollet-Ramírez, Frank (2019)
The research applied the concepts and strategies of the new model of strategic management using the Balanced Scorecard, integrated with other approaches on a broader and more comprehensive management scheme to influence the performance of the company Kaniman SRL in the city of Pucallpa, Peru, 2012 period; for this purpose the quantitative research methodology with quasiexperimental design was used, representing the research process in time or time series and technical analysis: univariate inferential; for assessing the performance of the company seventeen indicators as a measure of business performance, was used in the four dimensions of the Balanced Scorecard, which are: financial perspective, customer perspective, internal perspective and learning and growth perspective. establishing that the implementation of the proposed management model, positive influence on improving the performance of the company mentioned, determining the influence for the highest score of the values of the 17 indicators of the post test, relative to pre-test values with an increase of 19 % after the implementation of the proposed model of strategic management; therefore concluded that the effectiveness of the model lies in an understanding of its foundations, a complete program involving the corporation and an ongoing review of its results for the alignment to superior business performance.